The Malay historical urban landscape: a trajectory of the Bujang Valley site to Jugra, Selangor - Baniyamin, Nurhaya; Md Zain, Mazarina; Jahn Kassim, Puteri Shireen (Asian Scholars Network, 2022)
Malaysia is rich in heritage, primarily archaeological sites, historical buildings, monuments, artifacts, tangible, and intangible traditional and cultural heritage elements. Archaeotourism is one of the heritage tourism activities which is growing rapidlyand attracts many visitors to the Malaysian tourism industry. In alluring visitors to the destination, an archaeological site must offer an extraordinary experiential and continually to develop meanings as an attraction to increase the numbers of visitors. The issue of historical urban landscape in Nusantara has been defined for ‘colonial’-based cities, but not pre-colonial sites. The primal and axial role of rivers, mountainsand mounds in Malay history reflect not only its topographical and physical axis, but resonates from a time when the mountain claimed a primal role in the cosmology and cosmography of place. This paper attempts to find similarities between the early kingdom of Malay Peninsula, Bujang Valley archaeology site, 16thcentury Kota Melaka and 19thcentury Jugra, which reflect the historic landscape features and its uniqueness of architecture, with discovery of the remains archaeology artefact with another site in Selangor. Jugra site which similarly has the urban landscape consisting of mountain, river and key public structures. The urban form configuration and the natural setting identifies a continuity and model between a pre-Islamic and colonial-era model with similarity on the topographical, physical and historical attributes of each cultural and heritage element. This study emphasizes that by determining the historical urban landscape perspective in heritage sites, including natural physical landform, architectural archetypes, and significance in multicultural historical values, its key elements can be extracted for developing national identity and promoting heritage sites in the Malaysian tourism industry for its intangible intellectual, emotional, and aesthetical reasons.